Respuesta :
Answer:
90
Step-by-step explanation:
5x – 2y + (7x – y)
Combine like terms
12x -3y
Let x = 7 and y = -2
12(7) -3(-2)
84 +6
90
Answer:
90
Step-by-step explanation:
Hi there!
We are given this expression:
5x-2y+(7x-y) and we want to evaluate it if x=7 and y=-2
First, let's combine like terms, as that will make it easier for when we substitute the values into the expression
Open up the parentheses
5x-2y+7x-y
Combine like terms
12x-3y
Now substitute 7 as x and -2 as y into the expression
12(7)-3(-2)
Multiply
84+6
Add
90
Hope this helps!